The Effectiveness of Integrated Unified Protocol for Transdiagnostic Treatment on the Self-Concept of Children with Internalized Behavior Problems - Hosseini , Maryam Sadat; Rezakhani, Simindokht; Jahangir, Pantea (KMAN Counseling & Psychology Nexus, 2024)
In recent years, the mental and emotional health of children has received increasing attention within the field of psychology, with a particular focus on behavioral problems. This study aims to investigate the effectiveness of the Unified Protocol for Transdiagnostic Treatment on the self-concept of children exhibiting internalized behavior problems. This study employed a semi-experimental design with pre-test, post-test, and follow-up assessments (2 months) and a control group. The statistical population comprised all children aged 8 to 10 years with internalized behavioral problems in Najaf Abad city in the second half of 2022. A total of 30 children were selected based on the inclusion criteria using a convenience sampling method and were randomly assigned to two groups of 15 participants each (experimental and control). The Children’s Self-Concept Scale (Piers-Harris, 1969) was used to measure self-concept. The experimental group received the Unified Protocol for Transdiagnostic Treatment (children’s version) for 15 sessions, each lasting 120 minutes, delivered weekly. The control group received no intervention. Data were analyzed using repeated measures analysis of variance (ANOVA). Repeated measures ANOVA indicated that the Unified Protocol for Transdiagnostic Treatment significantly improved the self-concept of children in the experimental group, with the effects remaining stable over time. The implementation of the Unified Protocol for Transdiagnostic Treatment can strengthen and improve the self-concept components in children with internalized behavioral problems. This intervention may therefore be considered an effective approach to enhancing self-concept and reducing psychological and behavioral disorders in this population.